The irretroativity of the new forest code and the jurisprudence of the supreme federal court - Silveira, Edson Damas; De Camargo, Serguei Aily Franco [UNESP] (Editora Dom Helder, 2018)
This paper points out some reflections about the constitutionality of the New Forestry Code, as viewed in the Brazilian Supreme Court judgement, performed in February of 2018. It is discussed the possibility of amnesty to environmental polluter agents, due to a misinterpretation of that legal diploma. Thus, starting from the analysis of the discourse of the votes of the Supreme Court Ministers, it is intended to subsidize a conciliatory thesis to allow the understanding that the prohibition of retroactivity in environmental matters does not limit the legislator. In the same way, the balance between the most beneficial retroactivity of the law and the need to repair environmental damage indicates that the hermeneutical path allows us to understand that the New Forest Code did not ameliorate the offenders but imposed new conditions to give full effect to the dictates of Article 225 of CF/88.
Keywords: Environmental Damage; Forest Code; Law 12,651 / 12; Nonretroactivity of the Law